ANALISA WEBSITE FKIP UNSIKA BERDASARKAN PRINSIP INTERAKSI MANUSIA DAN KOMPUTER: FKIP UNSIKA WEBSITE ANALYSIS BASED ON PRINCIPLES OF HUMAN AND COMPUTER INTERACTION - Putri Riyandoro, Affani; Ahzka Nabbilah Tuzzahrah; Azhari Ali Ridha (Universitas Islam Balitar, 2023)
The website of the Fakultas Keguruan dan Ilmu Pendidikan Unsika functions as a platform for FKIP Unsika students to access information related to lectures. The purpose of analyzing the FKIP Unsika Website is to understand the relationship between system functions based on the principles and paradigms of Human and Computer Interaction (HCI). In analyzing the Website interface design, the author uses a heuristic evaluation method that evaluates human, technological, usability, and ergonomic aspects. The data used in this research was obtained through distributing questionnaires to respondents who have experience in designing and creating websites, and have a background in informatics. The results show that the rules in the heuristic evaluation method used, such as Visibility of system status, Match between the system and the real world, User control and freedom, Consistency and standards, Recognition rather than recall, and Flexibility and efficiency of use, have not been fully met because there are still problems that need to be fixed.